Rancangan Kawasan Kota Tua Teluk Betung Selatan Sebagai Destinasi Wisata Kota Bandar Lampung - Andyzon Octadinata; Citra Persada; Endro Prasetyo (Universitas Muslim Indonesia, 2020)
The Design Area Of South Teluk Betung Old Town As Tourism Destination In Bandar Lampung City Bandar Lampung City has an old town area which is located in the South Teluk Betung District. This town has existed since 1839, and the area is a center of trade and services which became the forerunner to the formation of the Capital of Bandar Lampung before being moved to Tanjung Karang. The South Teluk Betung Old Town area has heritage buildings with some variety of architectural styles such as: Thay Hin Bio Temple with Chinese architecture style, Jami